1998
DOI: 10.1007/s004120050320
|View full text |Cite
|
Sign up to set email alerts
|

A new look at kinetochore structure in vertebrate somatic cells using high-pressure freezing and freeze substitution

Abstract: Three decades of structural analysis have produced the view that the kinetochore in vertebrate cells is a disk-shaped structure composed of three distinct structural domains. The most prominent of these consists of a conspicuous electron opaque outer plate that is separated by a light-staining electrontranslucent middle plate from an inner plate associated with the surface of the pericentric heterochromatin. Spindle microtubules terminate in the outer plate and, in their absence, a conspicuous corona of fine f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
90
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 49 publications
4
90
1
Order By: Relevance
“…Hec1 recruits Zwint-1 and ZW10 to kinetochores for chromosome segregation It is known that the kinetochores comprise several layers of structures that are likely assembled in a hierarchical order by multiple copies of distinct protein subcomplexes (Brinkley and Stubblefield, 1966;Zinkowski et al, 1991;McEwen et al, 1998;Kniola et al, 2001;De Wulf et al, 2003). Both Hec1 and Zwint-1 are the outer kinetochore components, while ZW10 is present at the fibrous corona (Kitagawa and Hieter, 2001;Chan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Hec1 recruits Zwint-1 and ZW10 to kinetochores for chromosome segregation It is known that the kinetochores comprise several layers of structures that are likely assembled in a hierarchical order by multiple copies of distinct protein subcomplexes (Brinkley and Stubblefield, 1966;Zinkowski et al, 1991;McEwen et al, 1998;Kniola et al, 2001;De Wulf et al, 2003). Both Hec1 and Zwint-1 are the outer kinetochore components, while ZW10 is present at the fibrous corona (Kitagawa and Hieter, 2001;Chan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopy studies have revealed that the plus ends of spindle microtubules terminate in the outer kinetochore of vertebrate cells (McEwen et al, 1998;VandenBeldt et al, 2006), suggesting that nucleolin covering the outermost layer of kinetochores could affect the kinetochore-microtubule attachments. We found that cells depleted of nucleolin were delayed at prometaphase with misaligned or non-aligned chromosomes and defects in chromosome biorientation.…”
Section: Nucleolin Is Involved In Chromosome Congressionmentioning
confidence: 99%
“…Activation of Aurora-B during mitosis can correct chromosome attachment errors by selective disassembly of kinetochoremicrotubule fibers, thereby activating the spindle checkpoint until all the chromosomes make proper bipolar attachments to the mitotic spindle. It is therefore probable that nucleolin depletion does not activate the checkpoint directly but rather causes an increase in syntelic attachments, which are changed into unattached kinetochores by Aurora-B.Electron microscopy studies have revealed that the plus ends of spindle microtubules terminate in the outer kinetochore of vertebrate cells (McEwen et al, 1998;VandenBeldt et al, 2006), suggesting that nucleolin covering the outermost layer of kinetochores could affect the kinetochore-microtubule attachments. We found that cells depleted of nucleolin were delayed at prometaphase with misaligned or non-aligned chromosomes and defects in chromosome biorientation.…”
mentioning
confidence: 99%
“…The corona on unbound kinetochores was clearly visible and similar to control unbound kinetochores (Figure 2e). Because detergent extraction and conventional fixation mask fine structure alterations (McEwen et al, 1998), we chose not to perform a more detailed analysis at this time. The injected anti-CENP-E antibodies were detected with Cy-5-conjugated anti-rabbit antibodies (c and f).…”
Section: Kinetochore Microtubule Binding In Anti-cenp-einjected Cellsmentioning
confidence: 99%